The Influence of Raw Materials and Technology on Production Output of MSMEs Slondok Crackers in Sumurarum Village, Grabag District, Magelang Regency - Nur Fiana; Wijayanti; Dedi Runanto (www.amertainstitute.com, 2025)
This research aims to examine the influence of Raw Materials and Technology on Production Output in micro, small, and medium enterprises (MSMEs) producing Slondok Crackers in Sumurarum Village, Grabag District, Magelang Regency, Central Java. In an industry, achieving success in the production process highly depends on production factors. The production factors of Raw Materials and Technology are among the key components that, when combined well, can lead to optimal production results. Well-managed production factors can enhance quality and significantly improve production output. This study uses a quantitative approach with a survey method. The population in this study consists of slondok cracker craftsmen in Sumurarum Village, with a sample of 100 respondents. Data collection was conducted thru questionnaires and analyzed using SPSS 29.0 for Windows with the multiple linear regression method. The research results show that raw materials have a positive effect on production output, and technology also has a positive effect on production output. The results of the multiple linear regression analysis indicate that raw materials have an influence of 63.2% on production output, while technology has an influence of 30.2%. Furthermore, based on the research results, it shows that the variables of raw materials and technology simultaneously have a positive and significant effect on production output. These findings highlight the importance of effectively managing raw materials and technology to enhance the productivity of MSMEs